2022
DOI: 10.3389/fimmu.2022.927955
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter baumannii Outer Membrane Protein A Induces Pulmonary Epithelial Barrier Dysfunction and Bacterial Translocation Through The TLR2/IQGAP1 Axis

Abstract: Pulmonary epithelial barrier dysfunction is a critical pathophysiological process in pneumonia and associated invasive infections, such as those caused by Acinetobacter baumannii. However, the mechanisms underlying A. baumannii-induced pulmonary epithelial barrier dysfunction and bacterial translocation remain unclear. In this study, lungs of mice and A549 human epithelial cell monolayers were challenged with the A. baumannii wild-type strain and an outer membrane protein A (ompA) deletion strain. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…sepsis), particularly in immunosuppressed patients or those on mechanical ventilation, leading to a high mortality rate [ 7 ]. Virulence factors such as OmpA, lipopolysaccharides, and capsule [ 8 , 9 ] mediate host colonization and damage. Especially, capsular exopolysaccharide and associated mucoid phenotype have emerged as a universal virulence factor owing to several observations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…sepsis), particularly in immunosuppressed patients or those on mechanical ventilation, leading to a high mortality rate [ 7 ]. Virulence factors such as OmpA, lipopolysaccharides, and capsule [ 8 , 9 ] mediate host colonization and damage. Especially, capsular exopolysaccharide and associated mucoid phenotype have emerged as a universal virulence factor owing to several observations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the K. pneumoniae culture filtrate identified 160 high-confidence proteins ( Table S1 ), of which 35 were identified to have possible effects on fungal development ( Table 1 ) and three of which (putative lipoprotein, outer membrane protein A and chaperone protein DnaK) were also bound to the fungal mycelia. Outer membrane protein A is essential for A. baumannii cell attachment to Candida albicans filaments and A549 human alveolar epithelial cells [ 23 ] and has been demonstrated to induce leaky barriers in murine lungs and human A549 cells without affecting cell viability [ 24 ]. Elongation factor Tu was identified in the K. pneumoniae culture filtrate is involved in bacterial virulence and is associated with adhesion to host extracellular matrix components.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis revealed that five proteins involved in the biosynthesis of gliotoxin were increased in abundance; glutathione S-transferase (+6.17 fold), non-ribosomal peptide synthase (+3.67 fold), O-methyltransferase (+3.5 fold), gamma-glutamyl acyltransferase (+2.89 fold) and thioredoxin reductase (+2.33 fold). The increase in gliotoxin production may be attributed to the physical binding of outer membrane protein A, due to its ability to induce leakage in epithelial cells [ 24 ] in a similar manner to fungistatic concentrations of amphotericin B which increases A. fumigatus permeability and stimulates de novo gliotoxin biosynthesis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outer membrane proteins (OMPs) such as OmpA help in attachment and internalization into host epithelial cells. In addition to this, OmpA induces secretion of apoptotic factors inside the host cell that initiates the apoptosis process leading to cell death (Choi et al, 2008a;Choi et al, 2008;Moon et al, 2012;Zhang et al, 2022). Capsular exopolysaccharides in A. baumannii protect the pathogen from environmental and host-mediated stresses, and the composition determines the degree of virulence (Tipton and Rather, 2017;Singh et al, 2019;Talyansky et al, 2021).…”
Section: Virulence and Pathogenesis Factorsmentioning
confidence: 99%
“…It causes downregulation and internalization of Ecadherin, an important adhesion junction protein, thereby increasing lung epithelial permeability. It also causes actin reorganization in lung epithelial cells (Zhang et al, 2022).…”
Section: Virulence and Pathogenesis Factorsmentioning
confidence: 99%